A Real-Time Data Set for Switzerland - Ronald Indergand; Stefan Leist (Swiss Journal of Economics and Statistics, 2014)
Accessibility of real-time data is crucial for applied macroeconomic researchers who aim at evaluating forecasts, policy decisions or the accuracy of initial data estimates. To the extent of our knowledge, no appropriate and comprehensive real-time data set has been published for Switzerland so far. This paper introduces such a data set, which can be downloaded online. The balanced database includes quarterly, seasonally adjusted vintages of the most important economic variables on the national level. A short analysis of data revisions is provided for quarterly GDP. The magnitude of revisions are comparable to other countries such as the Euro Area or the United States. However, revision policy may differ considerably and potentially influence a statistical analysis.
Keywords: C82; E30; 330; real-time data; data revisions